2020
DOI: 10.2147/nss.s278752
|View full text |Cite
|
Sign up to set email alerts
|

<p>Watch-PAT is Useful in the Diagnosis of Sleep Apnea in Patients with Atrial Fibrillation</p>

Abstract: Background: Early diagnosis and treatment of sleep apnea in patients with atrial fibrillation (AF) is critical. The WatchPAT (WP) device was shown to be accurate for the diagnosis of sleep apnea; however, studies using the WatchPAT device have thus far excluded patients with arrhythmias due to the potential effect of arrhythmias on the peripheral arterial tonometry (PAT) amplitude and pulse rate changes. Purpose: To examine the accuracy of the WP in detecting sleep apnea in patients with AF. Patients and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…If one compares the mean/median/interquartile range/90th percentile of the hypoxic burden (percentage of total sleep time with SpO 2 < 90%), the results show 11/2/0-10/40% vs 4/0.2/0-2/10% using PSG vs PAT, respectively, or a significantly higher value using PSG (Wilcoxon signed rank test, P < .0001). Overall, we found that the sources of error were multiple and were represented by several major categories: (1) epochs of discordance between actual sleep and PAT-derived sleep (not a surprise because other studies have showed low accuracy for epoch-by-epoch sleep staging, eg, 62% in the study by Tauman et al 8 ), (2) periods excluded from analyses by the WatchPAT200 device because of various artifactual signals, (3) pulse oximetry artifacts, and (4) under-or overscored PAT respiratory events, 9 the latter leading clinically to either under-or overestimation.…”
mentioning
confidence: 76%
“…If one compares the mean/median/interquartile range/90th percentile of the hypoxic burden (percentage of total sleep time with SpO 2 < 90%), the results show 11/2/0-10/40% vs 4/0.2/0-2/10% using PSG vs PAT, respectively, or a significantly higher value using PSG (Wilcoxon signed rank test, P < .0001). Overall, we found that the sources of error were multiple and were represented by several major categories: (1) epochs of discordance between actual sleep and PAT-derived sleep (not a surprise because other studies have showed low accuracy for epoch-by-epoch sleep staging, eg, 62% in the study by Tauman et al 8 ), (2) periods excluded from analyses by the WatchPAT200 device because of various artifactual signals, (3) pulse oximetry artifacts, and (4) under-or overscored PAT respiratory events, 9 the latter leading clinically to either under-or overestimation.…”
mentioning
confidence: 76%
“…Screening for SDB was performed using the WatchPAT-200U (WP) (Itamar Medical, Caesarea, Israel). The WP system is a home sleep apnea testing (HSAT) device which has been shown to be accurate for diagnosing SDB, also in patients with AF [16] . It consists of a wrist-worn device with a finger probe that obtains peripheral arterial tonometry (PAT) signals and oxygen saturation levels, a snoring and body position sensor that is positioned under the sternal notch and accelerometer that is embedded in the wrist unit ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The WP provides accurate sleep/ wake and REM/NREM discrimination together with non-REM categorization into deep and light sleep. In addition, the WP provides accurate measurements of snoring and body position [14]. The device is attached to the patient's wrist, like a watch [15].…”
Section: Methodsmentioning
confidence: 99%